Decree of the minister of tourism No. 26/2014 Amending decree No. 533/2012 which amending decree No. 209/2009 on issuing the executive regulations of law No. 38/1977 on the organization of tourist companies / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 2/2014